PENGARUH LATIHAN PLYOMETRIC TERHADAP PENINGKATAN KEMAMPUAN JUMPING SMASH BOLA VOLI PADA SISWA EKSTRAKURIKULER SMA NEGERI 1 BAKTIRAJA - Banjarnahor, Yonatan; Maya Sari, Dewi; Puspa Sari, Liliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The abstract is written in 1 paragraph without citation, footnotes, and abbreviations. Volleyball is a sport that demands excellent physical components, particularly leg muscle explosive power to execute effective smash techniques. The main problem identified at SMA Negeri 1 Baktiraja is the low vertical jump ability of extracurricular students, where preliminary tests showed that 82% of students were in the moderate category, while only 18% were in the good category. This condition directly hinders the effectiveness of attacking performance during matches. This study aims to analyze the effect of plyometric training combining squat jump, depth jump, and hurdle jump on improving volleyball jumping smash ability. This study employed a quasi-experimental method with a one-group pretest-posttest design. A sample of 22 male students was selected using purposive sampling technique. Data were collected through vertical jump tests before and after treatment over 14 meetings, then analyzed using normality tests and paired sample t-tests. The results showed a significant increase in the pretest mean value from 55.77 to 63.36 in the posttest. Statistical analysis yielded a t-count of -26.71 with a significance of p = 0.00 (< 0.05), indicating a significant difference between before and after treatment. Furthermore, a correlation coefficient of 0.96 indicates a very strong relationship. In conclusion, plyometric training is proven effective in increasing vertical jump and is recommended as a routine training method to improve athlete performance. Keywords: Plyometric training, jumping smash, volleyball, vertical jump, muscle power. Keywords: Plyometric training, jumping smash, volleyball, vertical jump, muscle power.